Technique for Teaching Parametric 3D Furniture Modelling (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The object of the study is the technique for teaching students 3D modelling of furniture products using general-purpose CAD systems.The aim of the research is to improve the technique for teaching students of technical and designer specialisations parametric three-dimensional modelling of furniture products using general-purpose CAD systems. In this context, particular importance is attached to the appropriate selection of a furniture product that serves as the initial example for introducing students to the use of three-dimensional parametric CAD.The subject of the study involves defining the requirements for a furniture product intended for initial student training, determining the sequence of constructing its 3D model, and identifying approaches to developing task variants and the subsequent extension of assignments through a transition from individual to collective group work.The research is based on the generalisation of experience gained during the implementation of a collective group project on the development of school furniture by students enrolled in the educational programme Woodworking and Furniture Technologies at the bachelor’s level of higher education at the State Biotechnological University (Kharkiv, Ukraine), as well as on the results of an analysis of relevant literature sources.The feasibility of using pupils’ desks and chairs as educational objects for the initial training of students in parametric 3D modelling has been substantiated.It is proposed to supplement the well-known four-stage teaching methodology (consisting of creating a 3D model based on detailed drawings of component parts, modifying parts, varying dimensions, and expanding the product range) with an additional stage. This stage involves the creation of structurally distinct products with similar functional purposes, or the completion of a collective group assignment focused on designing other items of furniture (preferably for furnishing the same interior space). In this approach, students independently form groups of two to three members, select and model specific furniture items, and collaboratively develop a functionally complete furniture set while coordinating key structural, technological, and aesthetic solutions.The obtained results may be applied in updating educational programmes in furniture design, interior design, and wood processing technologies.
Keywords: furniture; model; CAD; parametrisation; education; methodology; form generation